Representações sociais da tuberculose: um estudo sócio-antropológico - Souza, Roberto Martins de (2008)
This thesis proposes a reflection on the process of exclusion of patients with pulmonary tuberculosis in a region of Itaquera BHU (Basic Health Unit), in São Paulo. We assumed that the disease and its cure constitute a complex phenomenon biological, psychological, sociological and cultural dimensions. We believe that adherence to treatment and the healing process itself go much beyond the effectiveness of drug or any change in living conditions, and so involving that set of dimensions. Thus, the situations of isolation and social exclusion are extremely adverse, can cause stress, fear, shame and can also create real obstacles as for the remission of the disease as for the resumption of life in its condition prior to the illness. In light of situation we can understand it as a total social fact (M. Mauss), the anthropological approach might be revealing. In other words, with such theoretical support we believe to have batter conditions to rescue the state of health / disease in its complexity. This work has been developed from literature, survey data, interviews and observation, the work field has been developed in a qualitative perspective preferring the prospect of the main involved, that is, seeking representations of the patients themselves, on the binomial health and disease, tuberculosis and its repercussions in the various delays of their life and their perception of exclusion. The professionals of the BHU (Basic Health Unit) were equally interviewed also seek their representations about the exclusion